Exploring the clinical features of minimally verbal autistic children - Guerrera, Silvia; Fucà, Elisa; Petrolo, Emanuela; De Stefano, Andrea; Casula, Laura; Logrieco, Maria Grazia; Valeri, Giovanni; Vicari, Stefano (Frontiers in Psychiatry, 2025)
IntroductionIt is recognized that around 25-30% of autistic children do not develop functional speech and remain minimally verbal beyond the age of 5. However, little is known about the clinical characteristics of this group.MethodsWe retrospectively examined a sample of 189 autistic children and adolescents classified as minimally verbal (mean age: 7.37 ± 1.51; 152 males, 37 females) and compared them with a group of 184 verbal autistic children and adolescents (mean age: 7.71 ± 2.52; 160 males, 24 females). We considered intellectual functioning, severity of autism, emotional and behavioural problems, and parenting stress.ResultsChildren in the minimally verbal group exhibited significantly lower nonverbal Intelligent Quotient and an increase in restricted repetitive behaviours compared to the verbal group. Exploring potential differences in emotional and behavioural problems, the verbally group showed higher levels of anxiety symptoms. In addition, minimally verbal group showed high score of parenting stress.DiscussionThis study highlights the importance of accurately characterizing minimally verbal autistic children and adolescents to facilitate the identification of specific and individualized interventions based on individual functioning profiles.